Decadal trends in abundance, size and condition of Antarctic toothfish in McMurdo Sound, Antarctica, 1972–2011. Issue 3 (19th May 2012) - Ainley, David G; Nur, Nadav; Eastman, Joseph T; Ballard, Grant; Parkinson, Claire L; Evans, Clive W; DeVries, Arthur L.
Abstract We report the analyses of a dataset spanning 39 years of near‐annual fishing for Dissostichus mawsoni in McMurdo Sound, Antarctica, 1972–2011. Data on total length, condition and catch per unit effort (CPUE) were derived from the > 5500 fish caught, the large majority of which were measured, tagged and released. Contrary to expectation, the length frequency of the McMurdo Sound catch was dominated by fish in the upper two‐thirds of the overall distribution exhibited in the industrial catch for the Ross Sea shelf. Fish length and condition increased from the early 1970s to the early 1990s and then decreased. Fish length positively correlated with Ross Sea ice extent in early spring, a relationship possibly caused by more ice encouraging larger fish to move farther south over the shelf and into the study area. Fish condition positively correlated with the amount of open water in the Ross Sea during the previous summer (Feb), perhaps reflecting greater availability of prey with the higher productivity that more open water brings. Decreasing fish size corresponds to the onset of the fishery, which targets the large individuals. CPUE was constant through 2001 and then decreased dramatically. We hypothesize that this decrease is related to the industrial fishery, which began in the 1996–97 austral summer, and concentrates effort over the ice‐free Ross Sea continental slope. As a result of limited prey choices and close coupling among mesopredators of the region, Antarctic toothfish included, the fishery appears to be dramatically altering the trophic structure of the Ross Sea.